Collective Identity and Cultural Resistance in Contemporary Chicana/o Autobiography - Velasco, Juan.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
The first book length study of this genre, Collective Identity and Cultural Resistance in Contemporary Chicana/o Autobiography facilitates new understandings of how people and cultures are displaced and reinvent themselves. Through the examination of visual arts and literature, Juan Velasco analyzes the space for self-expression that gave way to a new paradigm in contemporary Chicana/o autobiography. By bringing together self-representation with complex theoretical work around culture, ethnicity, race, gender, sex, and nationality, this work is at the crossroads of intersectional analysis and engages with scholarship on the creation of cross-border communities, the liberatory dimensions of cultural survival, and the reclaiming of new art fashioned against the mechanisms of violence that Mexican-Americans have endured.
Preface -- Introduction: Beyond the Hunger of Memories -- Automitografia -- Crossings -- Culture As Resistance -- Making Familia From Scratch -- The New Mestizas -- Canicular Consciousness -- Bibliography.
Keywords: Fiction; Literature, Modern-20th century; Postcolonial/World Literature; Twentieth-Century Literature